Psychological Well-Being in Chinese College Students During the COVID-19 Pandemic: Roles of Resilience and Environmental Stress - Tan, Yuanfa; Huang, Chienchung; Geng, Yun; Cheung, Shannon P.; Zhang, Shuyan (Frontiers in Psychology, 2021)
Psychological well-being is an important indicator of well-being and has been found to be associated with a multitude of positive life outcomes. Using data collected from 1,871 Chinese college students from September 23 to October 5, 2020, this study examined students' psychological well-being during the COVID-19 pandemic and investigated how resilience and pandemic-related environmental stress may affect psychological well-being. Results showed that resilience had strong positive effects on psychological well-being during the pandemic. Meanwhile, environmental stress had a moderate effect and marginally reduced psychological well-being. The magnitudes of the estimates suggested that increasing resilience can effectively buffer the negative effect of environmental stress on psychological well-being.